Pennybaker School is revolting - Brown, Jennifer, 1972- (Bloomsbury Children's Books, 2018)
Strange things are happening at Pennybaker School for the Uniquely Gifted, and sixth-grader Thomas Fallgrout must stage a revolution to set them right.